Enhanced photonic spin Hall effect in Dirac semimetal metamaterial enabled by zero effective permittivity. (5th March 2023) - Da, Haixia; Song, Qi; Hu, Pengya; Ye, Huapeng
Abstract: With the recent discovery of three dimensional Dirac semimetals, their integrations with the optoelectronic devices allow the novel optical effects and functionalities. Here, we theoretically report the photonic spin Hall effect in a periodic structure, where three dimensional Dirac semimetals and the dielectric materials are assembled into the stack. The incident angle and frequency dependent spin shift spectrum reveals that the spin shifts of the transmitted wave in this structure emerge the obvious peaks and valleys for the horizontal polarized wave and their magnitudes and positions display a distinct dependence on the incident angle around the specific frequency. These observations originate from its zero value of the effective perpendicular permittivity and its greatly reduced transmission in the multilayered structure, whose mechanism is different from those in the previous works. Moreover, both the peaks and valleys of the transmitted spin shift are significantly sensitive to the Fermi energy of three dimensional Dirac semimetals, whose magnitudes and positions can be tuned by varying it. Our results highlight the vital role of three dimensional Dirac semimetals in their applications of the spin photonic devices and pave the way to explore the tunable photonic spin Hall effect by engineering their Fermi energies.